2009
DOI: 10.3201/eid1504.081329
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Diseases Endemic to the Amazon Region of Brazil, 2001–2006

Abstract: In Brazil, reportable diseases are the responsibility of the Secretariat of Health Surveillance of the Brazilian Federal Ministry of Health. During 2001During -2006, to determine incidence and hospitalization rates, we analyzed 5 diseases (malaria, leishmaniasis [cutaneous and visceral], dengue fever, leprosy, and tuberculosis) that are endemic to the Amazon region of Brazil. Data were obtained from 773 municipalities in 3 regions. Although incidence rates of malaria, leishmaniasis, tuberculosis, and leprosy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 11 publications
(6 reference statements)
1
20
1
3
Order By: Relevance
“…Supervised administration is still very important to ensure treatment, prevent disability, and control possible adverse effects, avoiding treatment abandonment or even helping patients who had interrupted treatment to resume it in a timely manner. 15,16,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervised administration is still very important to ensure treatment, prevent disability, and control possible adverse effects, avoiding treatment abandonment or even helping patients who had interrupted treatment to resume it in a timely manner. 15,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…However, complete removal of fragments of bacilli depends on cellular immunity, which is depressed or absent in multibacillary leprosy patients, causing risk of erythema nodosum leprosum and manifestation of disability. 15,17 …”
Section: Discussionmentioning
confidence: 99%
“…Deve-se ressaltar ainda que, mesmo com o aumento explosivo do número de casos e com o aumento do percentual de P. falciparum, a letalidade total nunca foi superior a 0,02%, o que vem ao encontro da redução da mortalidade por malária em todo o país nas últimas décadas. Sob certo aspecto, isso reflete a relativa eficácia de algumas ações de controle (26). No período estudado, de 11 anos estudados, houve uma tendência de diminuição da infecção por P. falciparum, ainda que não significativa, provavelmente em função da maior queda apenas nos últimos 2 anos, depois da introdução de artesunato/mefloquina, ainda que o impacto isolado dessa medida não possa ser avaliado com base nos dados apresentados.…”
Section: Figura 4 Mapa Hidrográfico De Cruzeiro Do Sul E Redondezasunclassified
“…4 Leishmania (Viannia) guyanensis is the most prevalent parasite in the region. 9 The city of Manaus is the largest human settlement located within the Amazon rain forest, with a population of approximately 1.7 million inhabitants. Early descriptions indicated that ATL is transmitted to human beings either within or in regions surrounding rain forest 10 or in the peridomiciles of those individuals living in the outskirts of the city.…”
Section: Introductionmentioning
confidence: 99%